Numerical experiments on neon soft x-ray optimization of AECS-PF2 plasma focus device - Al Hawat, Sh.; Akel, M.; Lee, S. (Springer US, 2011)
Numerical experiments have been investigated on modified AECS-PF2 with neon filling gas using the latest version of Lee model. The model was applied to characterize the 2.8 kJ plasma focus AECS-PF2, finding a neon soft X-ray yield (Ysxr) of 0.04 J in its typical operation. By numerical experiments the optimum combination of pressure of 0.57 Torr, anode length of 9 cm and anode radius of 1.57 cm was found. The optimum Ysxr found also to be 0.87 J. Thus we expect to increase the neon Ysxr of AECS-PF2 22-fold from its present typical operation; without changing the capacitor bank, merely by changing the electrode configuration. The Lee model code was also used to run numerical experiments on AECS-PF2 with neon gas for optimizing soft X-ray yield with reducing L0, varying z0 and ‘a’. From these numerical experiments we expect to increase the neon Ysxr of AECS-PF2 with reducing L0, from the present 0.04 J at L0 = 280 nH to maximum value of near 21 J at an achievable L0 = 15 nH at the pressure 2.8 Torr.